Probing the tunneling electron wave packet using the counter-rotating bi-circular fields. (16th August 2021) - Ge, Peipei; Han, Meng; Fang, Yiqi; Guo, Zhenning; Deng, Yongkai; Liu, Yunquan
Abstract: We experimentally measure the photoelectron momentum distributions of Ar atoms using two-color 800 nm ( ω ) + 400 nm (2 ω ) counter-rotating circularly polarized fields. By employing a weak fundamental circularly polarized field at 800 nm, the atomic potential barrier formed by the strong second harmonic field at 400 nm can be modulated. This introduces a spatially rotating temporal two-slit interferometry between the photoelectron wave packets tunneling from the modified barriers in the consecutive cycles. The modulation of the barrier would leave its imprint on the photoelectron interference pattern. In analogy to the analysis of the traditional optical interferometry, we perform the Fourier transform on the photoelectron interference. The modulation on the amplitude and phase of the electron wave packets induced by the weak fundamental field is retrieved.